The correlation between the absolute eosinophil count and the degree of asthma attack in children - Sumadiono Sumadiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: The presence of eosinophil in the blood count during an asthmatic attack has been the focus of study. More airway collapse occured in the eosinophil-positive patients, even the eosinophil-positive patients had a much higher incidence of respiratory failure and mechanical ventilation use than the eosinophil-negative group.Objectives: The purpose of this study was to know the correlation between the eosinophil count and the degree of the asthma attack in children.Methods: The subjects of the study were medical records of the asthmatic children who were hospitalized in Sardjito Hospital from 1995 to 2000. The asthma criteria was according to the international consensus. The asthma attack degree evaluation was according to GINA classification. Exclusion criterias: the patients with parasitic infection and no asthmatic respiratory disturbances patients.Results: There were 169 asthmatic patients hospitalized in Sardjito Hospital from 1995 to 2000. The incidence of the hospitalized asthmatic patients was tend to increase from year to year. The percentage of the asthmatic patients with mild and severe degree attack tend to increase. The mean of the absolute eosinophil count in some degree attack group were 143.4 in mild 221.9 and in severe degree attack group were 350.7.Conclusion: There was no significant difference of the absolute eosinophil count between some, mild and severe degree attack of the asthma patients.Keywords: asthma - children - eosinophil - degree of attack